Influence of the dental topical application of a nisin-biogel in the oral microbiome of dogs: a pilot study - Eva Cunha; Sara Valente; Mariana Nascimento; Marcelo Pereira; Luís Tavares; Ricardo Dias; Manuela Oliveira (PeerJ, 2021)
Periodontal disease (PD) is one of the most widespread inflammatory diseases in dogs. This disease is initiated by a polymicrobial biofilm in the teeth surface (dental plaque), leading to a local inflammatory response, with gingivitis and/or several degrees of periodontitis. For instance, the prevention of bacterial dental plaque formation and its removal are essential steps in PD control. Recent research revealed that the antimicrobial peptide nisin incorporated in the delivery system guar gum (biogel) can inhibit and eradicate bacteria from canine dental plaque, being a promising compound for prevention of PD onset in dogs. However, no information is available regarding its effect on the dog’s oral microbiome. In this pilot study, the influence of the nisin-biogel on the diversity of canine oral microbiome was evaluated using next generation sequencing (NGS), aiming to access the viability of nisin-biogel to be used in long-term experiment in dogs. Composite toothbrushing samples of the supragingival plaque from two dogs were collected at three timepoints: T1—before any application of the nisin-biogel to the animals’ teeth surface; T2—one hour after one application of the nisin-biogel; and T3—one hour after a total of three applications of the nisin-biogel, each 48 hours. After that, microbial profiling was performed by NGS of the V3V4 16s rRNA region. After only one application of the nisin-biogel to the oral cavity of dogs, a statistically significant reduction in microbial diversity was observed (T2) as well as a reduction of some bacterial species potentially related with distinct stages of PD, when compared with samples collected before any application (T1). However, after a total of three nisin-biogel applications (T3), a recovery of the microbial diversity was detected. In conclusion, the nisin-biogel may influence the canine oral microbiome. A reduction in some bacterial species potentially related with distinct stages of PD was observed. This pilot study will help to design a controlled in vivo clinical trial to evaluate nisin-biogel effect on dental plaque progression and canine periodontal indices evolution in a long-term application period.